CULTURE OF RAISING HANDS AS A GESTURE OF GREETING IN SABAH IN THE PERSPECTIVE OF THE VERSES OF THE QUR'AN GATHERING - Muhammad Fawwaz Faishal; Muhammad Hafizi Zul Arif; Mohd Firdaus Bin Madaim; Mohd Nazri Johari; Edi Hermanto (Almustofa Journal of Islamic Studies and Research, 2025)
This study explores the culture of raising one's hand as a greeting in Sabah society through the perspective of verses in the Qur'an that discuss gatherings (jamaah) and social interaction. This qualitative study uses the method of analyzing the content of the Qur'an and interviews with religious leaders and local communities in Sabah. The results of the study found that this practice is in line with general principles in the Qur'an such as respect (ihsan), maintaining relationships, and manners in meetings that emphasize compassion and politeness. Although not stated explicitly, this culture reflects universal Islamic values that support local traditions that do not conflict with Sharia law. The study concluded that the practice of raising the hand as a greeting in Sabah is a positive cultural manifestation that can be harmonized with Islamic teachings, while also strengthening community identity and unity. This investigation provides an integrative perspective between religious texts and local cultural practices.